Health Literacy among Patients with Diabetes Mellitus Type 2 in Northeast Area of Iran - Salimi 1, Masumeh; Sarchahi 2, Sourush; Zolfaghari 2, Pouneh; Daghyanous 3, Batoul; Mozaffari 3, Hossain; Montazeri 3, Masoumeh; Sohrabi 4*, Mohammad Bagher (Shahroud Journal of Medical Sciences, 2017)
Background: Type 2 diabetes mellitus (DM2) is the most common metabolic disorder with complex treatment, and adherence to its treatment requires sophisticated cognition, which includes health literacy. This study aimed to spread health literacy among patients with DM2 in northeast Iran.Methods: A cross-sectional survey was conducted among diabetic patients in Shahroud city of Iran in 2016. Multistaged cluster random sampling was used for 450 individuals with diabetes who were interviewed using two standard questionnaires on diabetes health literacy (TOFHLA and DNT15). Participants were enquired about their personal information (age, gender, level of education, etc.). Binary logistic regression analysis was used to identify risk factors for poor health literacy concerning diabetes prevention and control among patients with prediabetes.Results: The mean diabetes health literacy score was 44.0 (18.0–92.0). This score was higher among men than women (OR=1.623), and lowest literacy score was observed in respondents with less than 1 year of education (OR=13.041). The literacy score among diabetic patients with a family history of diabetes was higher than among those with no family history (OR=2.523).Conclusions: This study showed that health literacy related to diabetes prevention and control among diabetic individuals was rather low in Shahroud city. Appropriate health education for diabetic patients with low literacy should be incorporated into diabetes prevention efforts.